2015
DOI: 10.1007/s00428-015-1855-z
|View full text |Cite
|
Sign up to set email alerts
|

Indolent lymphomas in the pediatric population: follicular lymphoma, IRF4/MUM1+ lymphoma, nodal marginal zone lymphoma and chronic lymphocytic leukemia

Abstract: Indolent lymphomas in the pediatric population were discussed during the 2014 European Association for Haematopathology/Society of Hematopathology workshop in Istanbul, Turkey. This session was focused on pediatric-type follicular lymphoma (FL), and its differential diagnosis with the newly recognized entity of IRF4/MUM1+ lymphomas mainly involving Waldeyer's ring. The differential diagnosis between t(14;18) negative FL grade 1/2 and pediatric-type FL in adults was highlighted. The overlapping pathological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 51 publications
(79 reference statements)
3
66
0
16
Order By: Relevance
“…It has been suggested that t(14;18) 2 FL in adults often presents with low clinical stage and excellent prognosis, and therefore might represent a form of PTFL. 6,20 However, a recent study reported similar clinical features in FL with and without t(14;18) translocation. 21 The aim of this study was to perform a Polymerase chain reaction (PCR) amplifications for detecting monoclonal IGH chain gene rearrangements were performed according to the BIOMED-2 protocol 24 using a D4 fluorescent dye modified JH consensus primer (SigmaAldrich, St. Louis, MO) and 2 different concentrations (30 or 60 ng) of genomic DNA.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been suggested that t(14;18) 2 FL in adults often presents with low clinical stage and excellent prognosis, and therefore might represent a form of PTFL. 6,20 However, a recent study reported similar clinical features in FL with and without t(14;18) translocation. 21 The aim of this study was to perform a Polymerase chain reaction (PCR) amplifications for detecting monoclonal IGH chain gene rearrangements were performed according to the BIOMED-2 protocol 24 using a D4 fluorescent dye modified JH consensus primer (SigmaAldrich, St. Louis, MO) and 2 different concentrations (30 or 60 ng) of genomic DNA.…”
Section: Introductionmentioning
confidence: 93%
“…20,27 In contrast, the nodal counterpart is mostly follicular; does not express IRF4/MUM1 and rarely BCL2; and the genetic alterations are largely unknown. In the present study, we analyzed a large cohort with characteristic clinical and morphological features and demonstrated that the most frequent genetic alterations in nodal PTFL are mutations/ deletions in the TNFRSF14 gene.…”
Section: 26mentioning
confidence: 99%
“…Of note, this study did not specifically look at potential precursor lesions for the now clearly recognized pediatric type follicular lymphoma, an indolent type of follicular lymphoma mainly affecting children and young adults, notably lacking the classical t(14; 18) translocation and bcl-2 protein expression [24] .…”
Section: Discussionmentioning
confidence: 99%
“…The atypical follicles are comprised of a mixture of intermediate and larger-sized centroblastic lymphocytes with more immature chromatin often lending to an interpretation of higher-grade cytology and aggressive disease. Notably, these morphologic features are often not entirely specific and can show overlap with other lymphomas including pediatric marginal zone lymphoma (Quintanilla-Martinez et al, 2016). By the 2016 WHO classification, diffuse areas suggesting progression or transformation, exclude a diagnosis of pFL.…”
Section: Pathologymentioning
confidence: 99%